(untitled) (Bangladesh Journal of Medical Science, 2024)
Background: Stroke is a common neurological disorder with a high prevalence. The aim of this study was to determine the risk factor, prevalence, and association of types of strokes among diabetes and hypertension patients. Methods: A retrospective study was conducted in King Abdul Aziz, Qurayyat, Sakaka, and Tubarjal hospitals among stroke patients including both sexes within the age > 40 years. Type of stroke was identified by brain computed tomography scans or magnetic resonance imaging and risk factors for stroke and other details were noted on a checklist. Results: Out of 226 stroke patients considered for the present study, in which 48% were males and 52% were females. All lived in the Aljouf region. Most of the patients had risk factors which included Hypertension 49 (21.68%), Diabetes Mellitus 44 (19.46%), Combined (Hypertension and diabetes) 111 (49.11%), and Hyperlipidemia 22 (9.75%). Stroke patients > 60 years of age group showed a higher prevalence of ischemic stroke (p=0.001). The combined risk factor group also showed more prevalence of ischemic stroke (49.11%). Conclusion: Patient having both risk factor Hypertension and diabetes mellitus were major association with ischemic stroke. Majority of the patients with ischemic stroke age at onset > 60 year and irrespectively affected both males and females were equally. Bangladesh Journal of Medical Science Vol. 23 No. 01 January’24 Page : 171-178